A branch‐and‐price algorithm for the (k, c)‐coloring problem. Issue 4 (27th November 2014) - Malaguti, Enrico; Méndez‐Díaz, Isabel; José Miranda‐Bront, Juan; Zabala, Paula
<x xml:space="preserve">Abstract</x> In this article, we study the (k, c)‐coloring problem, a generalization of the vertex coloring problem where we have to assign k colors to each vertex of an undirected graph, and two adjacent vertices can share at most c colors. We propose a new formulation for the (k, c)‐coloring problem and develop a Branch‐and‐Price algorithm. We tested the algorithm on instances having from 20 to 80 vertices and different combinations for k and c, and compare it with a recent algorithm proposed in the literature. Computational results show that the overall approach is effective and has very good performance on instances where the previous algorithm fails. © 2014 Wiley Periodicals, Inc. NETWORKS, 2014 Vol. 65(4), 353–366 2015